Exclusion of Chromium(VI) Ion in Grueling Activated Carbon Fabricated from Manilkara zapota Tree Wood by Adsorption: Optimization by Response Surface Methodology. (23rd April 2022) - Sujatha, S.; Sivarethinamohan, R.; Oorkalan, A.; Senthilkumar, V.; Anuradha, B.; Veluchamy, B.; Prabhu, P.; Abdellattif, Magda H.; Dhahi Alsukaibi, Abdulmohsen Khalaf
Abstract : The current paper makes obvious the elimination of chromium(VI) ion, from wastewater via adsorption technique with activated carbon generated from Manilkara zapota tree (MZTWAC). Preliminarily MZTWAC has undergone characterization studies which uncovered the suitability of MZTWAC to expel chromium(VI) from aqueous solution. Batch adsorption experimentation was premeditated with the competence of central composite design (CCD) and it was executed. Response surface methodology (RSM) was the key optimization software to appraise the adsorptive chattels of MZTWAC engaged in removing chromium(VI) ion in aqueous solution which explored the interactions flanked between four expounding variables explicitly initial concentration of chromium(VI) ion, pH of the solution, MZTWAC dose and time of exposure, and contact time. The response variable that was concentrated in the study was adsorption capacity. It was deduced a polynomial in quadratic equation was documented amid the adsorption capacity and variables influencing the adsorption with R 2 = 0.9792 which was projected as the best suit for the adsorption process. ANOVA that is expanded as analysis of variance judged the connotation of adsorption process variables. 0.2 g of MZTWAC dosage has removed 87.629% chromium(VI) from aqueous solution. The enhancement of adsorption process reclined on the attainment of maximum adsorption capacity which further depends on the optimization of variables under consideration. This criterion was accomplished by the desirability function optimizing the process variables.